Architectural void is a revolution in the formation of the facades of digital architecture (Journal of Planner and Development, 2021)
Architecture has evolved through the ages as forms, relationships, materials and mechanisms according to the data of each era and up to the era of digital technology, where the change in proportions and aesthetic dimensions of contemporary architectural formation due to the capabilities of digitization has created innovative plastic properties using the void formation in the facades and the introduction of void as a formative and aesthetic element, which led to The emergence of new creative concepts and ideas that contradict traditional ideas and are consistent with the spirit of the times, led to a revolution in the world of architectural form at the level of (architectural ideas and the generation of shapes, materials and construction systems used), as a result of which new and innovative rules emerged to find the architectural form at the level of design and implementation to achieve the goals of the shape Creativity, such as regeneration and exclusivity, through discovering the formalities inherent in both mass and void, in pursuit of change and formal renewal and the appropriate effect on the recipient’s emotion. Digital Vacuum Modulation Rules). The aim of the research was to uncover the effect of the use of architectural void as a formative element in the interfaces of contemporary digital architecture on the rules of digital void formation and to reveal the characteristics and characteristics of the achieved void construction. Fine and the nature of the products generated from it and the author of the main vocabulary (factors affecting the formation of void, the characteristics of digital void creation, the rules of digital void formation), and its application to contemporary global, Arab and local architectural models on a qualitative scale aimed at knowing the effect of vocabulary on the selected samples and the percentage of their effectiveness in the properties of digital creation And to verify the main research hypothesis, which stipulated the possibility of generating a digital spatial model with contemporary characteristics by adopting integration in all elements and standards of digital design and implementation, as it is not possible to design and create digital spaces spatially using traditional methods, and vice versa, that is, it is not possible to implement digital spatial creation which is designed in ways Traditional obstetrics, and the conclusions showed that additional rules for architectural formation other than production emerged J appeared in the era of the industrial revolution that led to the breaking of traditional rules such as proportions, stereotypes and functionalities and the liberation of architectural formation from the rule of simple forms, standardization at the expense of multiplicity and diversity in formation will not be an imperative, and the emergence of new rules of formation called (digital formation rules).